VITALISASI SEKOLAH BERBASIS MODAL SOSIAL (Studi Kasus Penguatan Sekolah melalui Integrasi Modal Sosial dalam Kepemimpinan Sekolah di SMP Diponegoro Depok Sleman) - Suwadi Suwadi (Jurnal Pendidikan Agama Islam, 2015)
This study aims at finding the potential and the actuality of social capital in school leadership to improve the school vitality. This study was conducted by means of naturalistic qualitative approach. Thesetting was Diponegoro the private junior high schools in Sleman Regency. The subjects consisted of case of school established through purposive sampling techniques. The research procedure consisted of four steps by means of data collection methods in the form of observation, in-depth interviews, and document study. The data were using by inductive models, while the validity of the result met the criteria of credibility, transferability, dependability and conformability. The research findings are as follows. First,(a) the school social capital was using for improving the school vitality in the network elements, reciprocal relationship, mutual aid and trust. (b) The using of school social capital indicated the models of bridging and bonding the network elements, reciprocal relationship, mutual aid and trust. (c) The integration of social capital in school leadership could be seen from the school integrity in the academicdevelopment, human resources, funding system and the local contents. (d) The reason of utilizing the social capital was based on such values as silaturahim and syafaat in school leadership.